Paleozoic facies architecture in low-inclined mixed carbonate-siliciclastic sedimentary systems: depositional and tectonic signatures - Novak, Aleksandra, author; Egenhoff, Sven, advisor; Stright, Lisa, committee member; Schutt, Derek, committee member; von Fischer, Joe, committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.